Zirconia ceramic material and preparation method thereof
By using modified boron-doped combined materials such as molybdenum carbide and dispersants in the preparation of zirconia ceramics, the process flow is optimized, and the problems of high sintering temperature, long cycle and large energy consumption in the preparation of zirconia ceramics are solved, and high strength is achieved , wear resistance and tight structure of zirconia ceramic materials meet the demand of modern industry for high-performance ceramic materials.
Patent Information
- Application Number
- CN202411311169.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-20
AI Technical Summary
The existing preparation methods of zirconia ceramics have problems such as high sintering temperature, long cycle, large energy consumption, and difficulty in controlling microstructures, and it is difficult to improve the mechanical properties of the materials under low cost and environmentally friendly production conditions.
Using zirconia, modified boron doped molybdenum carbide, carbon nanotubes and dispersants (such as hydroxypropyl methylcellulose, polyvinyl alcohol), the raw material ratio is optimized through ball milling, grouting molding, hydraulic molding and sintering processes. and sintering system, zirconia ceramics with high strength, wear resistance and excellent microstructure were prepared.
It achieves the improvement of the mechanical properties and wear resistance of zirconia ceramics under lower cost and environmental protection conditions, reduces sintering defects, and obtains a tighter grain structure and better mechanical properties.
Smart Images

Figure BDA0005050707270000111 
Figure BDA0005050707270000112 
Figure BDA0005050707270000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic materials, and in particular to a zirconium oxide ceramic material and a preparation method thereof. Background Art
[0002] As a high-performance inorganic non-metallic material, zirconia ceramics have been widely used in aerospace, medical equipment, electronics, chemical industry, etc. due to their excellent mechanical properties, chemical stability and biocompatibility. The main component of zirconia ceramics is zirconium oxide, which stands out among many materials due to its unique phase change characteristics and excellent wear and corrosion resistance.
[0003] Traditional methods for preparing zirconia ceramics mainly include solid-phase sintering and liquid-phase sintering. The solid-phase sintering method is to prepare ceramics by sintering zirconia powder at high temperature, but the ceramics prepared by this method often have problems such as uneven grain size and microstructural defects, which affect the overall performance of the material. Although the liquid-phase sintering method can produce zirconia ceramics with fine grains and uniform structure, it has high requirements for temperature and atmosphere control during the sintering process, and the production cost is relatively high.
[0004] With the development of materials science and preparation technology, researchers are constantly exploring new preparation methods to optimize the performance of zirconia ceramics. For example, new preparation technologies such as sol-gel method, hydrothermal synthesis method, and spark plasma sintering are applied to the preparation of zirconia ceramics. These methods can quickly prepare high-performance zirconia ceramics at a lower temperature, and help to achieve precise control of the microstructure, thereby improving the mechanical properties and reliability of the material. Although the existing zirconia ceramic preparation technology has made certain progress, there are still some technical difficulties in the preparation process, such as high sintering temperature, long cycle, high energy consumption, and difficulty in microstructure control. In addition, how to further improve the mechanical properties of zirconia ceramics, reduce costs, and achieve green and environmentally friendly production through improvements in preparation methods remains the focus of materials science researchers and engineers.
[0005] Therefore, the present invention aims to provide a new type of zirconia ceramic and a preparation method thereof, which aims to prepare zirconia ceramics with higher strength, better wear resistance and better microstructure by optimizing the raw material ratio, improving the preparation process and sintering system, so as to meet the urgent demand of modern industry for high-performance ceramic materials. Summary of the invention
[0006] In view of the above-mentioned deficiencies in the prior art, the present invention provides a zirconia ceramic material and a preparation method thereof.
[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is:
[0008] A method for preparing a zirconium oxide ceramic material comprises the following steps:
[0009] Step 1, mixing: 60-100 parts by weight of zirconium oxide, 5-12 parts by weight of modified boron-doped molybdenum carbide, 1-3 parts by weight of carbon nanotubes, 2-5 parts by weight of cerium oxide, 5-10 parts by weight of a dispersant, and 80-150 parts by weight of a 40-60wt% ethanol aqueous solution are mixed and stirred to obtain a mixed solution; the mixed solution is ball-milled to obtain a ball-milled mixed solution;
[0010] Step 2: Forming: The ball milled mixture is subjected to slip injection molding to obtain a wet blank, and then the wet blank is pressed by a hydraulic press to obtain a green blank;
[0011] Step 3: Processing: cutting the green body to obtain a zirconia ceramic body;
[0012] Step 4: Sintering: Sintering the zirconia ceramic body to obtain a zirconia ceramic material.
[0013] Preferably, the ball milling rate in step 1 is 160-240 r / min, and the ball milling time is 2-5 h.
[0014] Preferably, the pressing pressure in step 2 is 180-260PMa, and the pressing time is 3-7min.
[0015] Preferably, the sintering temperature in step 4 is 1500-1800° C., and the sintering time is 3-6 hours.
[0016] Hydroxypropyl methylcellulose is a non-ionic cellulose ether with hydrophilicity. It can form a network structure in aqueous solution, which helps to improve the stability of the suspension. Polyvinyl alcohol is a water-soluble polymer with good dispersibility and can form a protective layer on the surface of solid particles to prevent particle aggregation.
[0017] When HPMC and PVA are mixed, they can work together using their different dispersion mechanisms to more effectively prevent the aggregation and sedimentation of zirconium oxide and other solid particles, thereby improving the dispersion stability of the entire system, achieving uniform physical and chemical changes in the subsequent calcination process, thereby obtaining a uniform microstructure and better material properties, reducing the risk of pores and crack defects formed due to particle aggregation during calcination, and thereby improving the tighter packing of ceramic materials, helping to optimize grain growth, thereby obtaining a finer and uniform grain structure, and improving the strength, toughness and compactness of ceramic materials.
[0018] Preferably, the dispersant includes at least one of hydroxypropyl methylcellulose, polyacrylic acid, polyvinyl alcohol, polyethylene glycol, and ammonium polyacrylate; further, the dispersant is composed of hydroxypropyl methylcellulose and polyvinyl alcohol in a mass ratio of 1:(1.2-2.5).
[0019] Molybdenum carbide can be used to obtain composite materials with small particle size at relatively low temperatures, and molybdenum carbide composite materials with different morphologies and structures can be prepared through doping and modification regulation. After molybdenum carbide is coated with silicon dioxide, it is surface-modified with N-(6-aminohexyl)aminomethyltriethoxysilane to obtain modified boron-doped molybdenum carbide.
[0020] Boron doping can change the microstructure of molybdenum carbide and increase its toughness. Modified boron-doped molybdenum carbide is a hard material. Its addition can improve the hardness and wear resistance of zirconia ceramics, promote grain refinement in zirconia ceramics and enhance the interface bonding between different phases, thereby improving the uniformity and mechanical properties of the material, and also helping to improve the wear resistance and structural stability of the material. In addition, the addition of modified boron-doped molybdenum carbide helps to optimize the sintering process, which may reduce the sintering temperature and increase the sintering rate, thereby saving energy and reducing production costs.
[0021] The introduction of silane coupling agent improves the dispersibility of boron-doped molybdenum carbide in the zirconia ceramic matrix, reduces particle aggregation, makes the ceramic material more uniform in microstructure, and helps to improve the density and strength of the material; the modified boron-doped molybdenum carbide can serve as the core of grain boundary formation during calcination, promotes grain growth and grain boundary formation, and the increase in the number of grain boundaries can improve the strength and toughness of the material; the boron-doped molybdenum carbide modified by silane coupling agent can react chemically with the surface of zirconia particles in zirconia ceramics during calcination to form a strong chemical bond, which enhances the bonding force between particles and helps to improve the overall compactness of the ceramic material. In addition, during the calcination process, the silane coupling agent can reduce the pores and defects in the ceramic material. Since the silane coupling agent improves the bonding force between particles, it helps to discharge gas and close tiny pores during the sintering process, thereby reducing the porosity in the material and improving the density of the material.
[0022] Preferably, the method for preparing the modified boron-doped molybdenum carbide comprises the following steps:
[0023] S1: uniformly mix molybdenum powder and carbon powder, add anhydrous ethanol to grind, press into tablets, and melt to obtain Mo2C matrix;
[0024] S2. Grinding the above Mo2C matrix with boric acid, calcining in a tube furnace, cooling to room temperature, washing, filtering and drying to obtain boron-doped molybdenum carbide;
[0025] S3: Disperse the above-mentioned boron-doped molybdenum carbide in an ethanol aqueous solution, stir evenly, add ammonia water and tetraethyl orthosilicate to stir and react, filter, wash, and dry to obtain silica-coated boron-doped molybdenum carbide; add N-(6-aminohexyl)aminomethyltriethoxysilane and stir to obtain modified boron-doped molybdenum carbide.
[0026] The specific reaction mechanism is as follows: S1 Preparation of Mo2C matrix: Molybdenum powder and carbon powder are used as raw materials and mixed evenly, and anhydrous ethanol is added for grinding. Ethanol, as a solvent and grinding aid, helps to form a uniform suspension and prevents the aggregation of powder particles. The mixed powder is pressed at a pressure of 120-180MPa to form a dense sheet. The pressed material is melted in an arc melting furnace. At high temperature, molybdenum and carbon react to form Mo2C. The reaction equation is: 2Mo+3C→Mo2C+C. In this process, carbon may partially exist in the form of graphite and form carbides with molybdenum.
[0027] S2 The above Mo2C matrix is mixed with boric acid and ground and calcined. The boric acid is decomposed at high temperature and doped into Mo2C to form boron-doped molybdenum carbide. Boron doping can improve the hardness and thermal stability of the material. The decomposition reaction of boric acid is: H3BO3→B2O3+3H2O
[0028] S3 boron-doped molybdenum carbide is dispersed in an ethanol aqueous solution, and ammonia and tetraethyl orthosilicate are added to heat and stir for reaction. Ammonia provides an alkaline environment, and tetraethyl orthosilicate is hydrolyzed to form silicon dioxide, which is coated on the surface of boron-doped molybdenum carbide to enhance its dispersibility and stability in the medium. Silica coating reaction: Si(OC2H5)4+4H2O→SiO2+4C2H5OH, surface modification: N-(6-aminohexyl)aminomethyltriethoxysilane is added for surface modification. The silane coupling agent forms a covalent bond with the surface of silicon dioxide and provides amino functional groups to enhance the interfacial activity and adhesion of the material.
[0029] Preferably, the method for preparing the modified boron-doped molybdenum carbide comprises the following steps:
[0030] S1: molybdenum powder and carbon powder are uniformly mixed in a mass ratio of (1.2-2.5): 1, anhydrous ethanol of 8-16wt% of the mass of the molybdenum powder is added, and the mixture is ground for 0.5-2h, pressed into a sheet at 120-180MPa for 2-6min, and then placed in an arc melting furnace for melting at a current of 400-800A and a melting time of 1-5min to obtain a Mo2C matrix;
[0031] S2 At room temperature, 8-14 parts by weight of the above Mo2C matrix and 2-5 parts by weight of boric acid are ground together for 20-60 minutes, and then placed in a nitrogen atmosphere tubular furnace at 800-900°C for calcination for 2-5 hours, cooled to room temperature, washed with 3-5 mol / L NaOH aqueous solution, filtered and dried to obtain boron-doped molybdenum carbide;
[0032] S3: Disperse 5-10 parts by weight of the above-mentioned boron-doped molybdenum carbide in 80-160 parts by weight of 55-65wt% ethanol aqueous solution, stir evenly, add 1-3 parts by weight of ammonia water and 0.5-2 parts by weight of tetraethyl orthosilicate, stir and react at 45-60°C and 400-700rpm for 4-8h, filter, wash and dry to obtain silica-coated boron-doped molybdenum carbide; add 0.5-2 parts by weight of N-(6-aminohexyl)aminomethyltriethoxysilane, stir at 40-55°C and 500-700rpm for 1-3h, centrifuge, wash and dry to obtain modified boron-doped molybdenum carbide.
[0033] A zirconia ceramic material is obtained by using any one of the above preparation methods.
[0034] Beneficial effects of the present invention: 1. The present invention provides a zirconia ceramic material and a preparation method thereof. By adding a dispersant, it is possible to effectively and more effectively prevent the aggregation and sedimentation of zirconia and other solid particles, thereby improving the dispersion stability of the entire system, achieving uniform physical and chemical changes in the subsequent calcination process, thereby obtaining a uniform microstructure and better material properties, reducing the risk of forming pores and crack defects due to particle aggregation during the calcination process, and thereby improving the tighter stacking of ceramic materials, which helps to optimize the growth of grains, thereby obtaining a finer and uniform grain structure, and improving the strength, toughness and compactness of ceramic materials.
[0035] 2. By adding modified boron-doped molybdenum carbide, the hardness and wear resistance of zirconia ceramics can be improved, which can promote grain refinement in zirconia ceramics and enhance the interface bonding between different phases, thereby improving the uniformity and mechanical properties of the material, and also helping to improve the wear resistance and structural stability of the material.
[0036] 3. The preparation method of the present invention is simple and low in cost, and can effectively reduce defects occurring during the sintering process. The prepared zirconia ceramic material has good mechanical properties, a dense structure, and good wear resistance. DETAILED DESCRIPTION
[0037] The above content of the present invention is further described in detail below in conjunction with specific implementation modes, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following embodiments.
[0038] Introduction of some raw materials in this application:
[0039] Carbon nanotubes were purchased from Guangzhou Jiushun New Materials Co., Ltd. with the brand name CN301C3.
[0040] Polyvinyl alcohol was purchased from Wuhan Runxingyuan Technology Co., Ltd., model PVA1788.
[0041] Molybdenum powder was purchased from Qinghe County Xingxin New Material Technology Co., Ltd., mesh number: 5000 mesh.
[0042] Carbon powder was purchased from Dongguan Longhuang Plastic Raw Materials Co., Ltd. with the brand name KD000EI.
[0043] Commercially available molybdenum carbide was purchased from Hebei Teng Bimetallic Materials Co., Ltd., 8000 mesh.
[0044] Example 1
[0045] A method for preparing a zirconium oxide ceramic material comprises the following steps:
[0046] Step 1, mixing: 80 parts by weight of zirconium oxide, 8 parts by weight of modified boron-doped molybdenum carbide, 2 parts by weight of carbon nanotubes, 3 parts by weight of cerium oxide, 7 parts by weight of dispersant, and 100 parts by weight of 50wt% ethanol aqueous solution are mixed and stirred to obtain a mixed solution; the mixed solution is placed in a ball mill for ball milling at a ball milling rate of 200r / min and a ball milling time of 3h to obtain a ball milled mixed solution;
[0047] Step 2, molding: the ball milled mixture is subjected to slip injection molding to obtain a wet blank, and then the wet blank is pressed by a hydraulic press at a pressure of 220PMa for 5 minutes to obtain a green blank;
[0048] Step 3: Processing: cutting the green body to obtain a zirconia ceramic body;
[0049] Step 4: Sintering: Sinter the zirconia ceramic body at 1650° C. for 5 h in a vacuum environment, cool naturally to room temperature, grind and polish to obtain a zirconia ceramic material.
[0050] The dispersant is composed of hydroxypropyl methylcellulose and polyvinyl alcohol in a mass ratio of 1:1.8.
[0051] The preparation method of the modified boron-doped molybdenum carbide comprises the following steps:
[0052] S1: molybdenum powder and carbon powder are uniformly mixed in a mass ratio of 2:1, anhydrous ethanol with a mass percentage of 10wt% of the molybdenum powder is added, and after grinding for 1 hour, the tablets are pressed at 150MPa for 4 minutes, and then placed in an arc melting furnace for melting, the current is 500A, and the melting time is 3 minutes to obtain a Mo2C matrix;
[0053] S2 At room temperature, 10 parts by weight of the above Mo2C matrix and 3 parts by weight of boric acid were ground together for 30 minutes, and then placed in a nitrogen atmosphere tube furnace at 850°C for calcination for 3 hours, cooled to room temperature, washed with 4 mol / L NaOH aqueous solution, filtered and dried to obtain boron-doped molybdenum carbide;
[0054] S3: Disperse 8 parts by weight of the above-mentioned boron-doped molybdenum carbide in 100 parts by weight of 60wt% ethanol aqueous solution, stir evenly, add 2 parts by weight of ammonia water and 1 part by weight of tetraethyl orthosilicate, stir and react at 50°C and 600rpm for 6h, filter, wash and dry to obtain silica-coated boron-doped molybdenum carbide; add 1 part by weight of N-(6-aminohexyl)aminomethyltriethoxysilane, stir at 50°C and 600rpm for 2h, centrifuge, wash and dry to obtain modified boron-doped molybdenum carbide.
[0055] Example 2
[0056] A method for preparing a zirconium oxide ceramic material comprises the following steps:
[0057] Step 1, mixing: 60 parts by weight of zirconium oxide, 5 parts by weight of modified boron-doped molybdenum carbide, 1 part by weight of carbon nanotubes, 2 parts by weight of cerium oxide, 5 parts by weight of dispersant, and 800 parts by weight of 40wt% ethanol aqueous solution are mixed and stirred to obtain a mixed solution; the mixed solution is placed in a ball mill for ball milling at a ball milling rate of 160r / min and a ball milling time of 2h to obtain a ball milled mixed solution;
[0058] Step 2, molding: the ball milled mixture is subjected to slip injection molding to obtain a wet blank, and then the wet blank is pressed by a hydraulic press at a pressure of 180PMa for 3 minutes to obtain a green blank;
[0059] Step 3: Processing: cutting the green body to obtain a zirconia ceramic body;
[0060] Step 4: Sintering: Sinter the zirconia ceramic body at 1500° C. for 3 h in a vacuum environment, cool naturally to room temperature, grind and polish to obtain a zirconia ceramic material.
[0061] The dispersant is composed of hydroxypropyl methylcellulose and polyvinyl alcohol in a mass ratio of 1:1.2.
[0062] The preparation method of the modified boron-doped molybdenum carbide comprises the following steps:
[0063] S1: molybdenum powder and carbon powder are uniformly mixed in a mass ratio of 1.2:1, anhydrous ethanol of 8wt% of the mass of the molybdenum powder is added, and the mixture is ground for 0.5h, pressed into a sheet at 120MPa for 2min, and then placed in an arc melting furnace for melting at a current of 400A and a melting time of 1min to obtain a Mo2C matrix;
[0064] S2 At room temperature, 8 parts by weight of the above Mo2C matrix was ground together with 2 parts by weight of boric acid for 20 minutes, and then placed in a nitrogen atmosphere tube furnace at 800°C for calcination for 2 hours, cooled to room temperature, washed with 3 mol / L NaOH aqueous solution, filtered and dried to obtain boron-doped molybdenum carbide;
[0065] S3: Disperse 5 parts by weight of the above-mentioned boron-doped molybdenum carbide in 80 parts by weight of 55wt% ethanol aqueous solution, stir evenly, add 1 part by weight of ammonia water and 0.5 parts by weight of tetraethyl orthosilicate, stir and react at 45°C and 400rpm for 4h, filter, wash and dry to obtain silica-coated boron-doped molybdenum carbide; add 0.5 parts by weight of N-(6-aminohexyl)aminomethyltriethoxysilane, stir at 40°C and 500rpm for 1h, centrifuge, wash and dry to obtain modified boron-doped molybdenum carbide.
[0066] Example 3
[0067] A method for preparing a zirconium oxide ceramic material comprises the following steps:
[0068] Step 1, mixing: 100 parts by weight of zirconium oxide, 12 parts by weight of modified boron-doped molybdenum carbide, 3 parts by weight of carbon nanotubes, 5 parts by weight of cerium oxide, 10 parts by weight of dispersant, and 150 parts by weight of 60wt% ethanol aqueous solution are mixed and stirred to obtain a mixed solution; the mixed solution is placed in a ball mill for ball milling at a ball milling rate of 240r / min and a ball milling time of 5h to obtain a ball milled mixed solution;
[0069] Step 2, molding: the ball milled mixture is subjected to slip injection molding to obtain a wet blank, and then the wet blank is pressed by a hydraulic press at a pressure of 260PMa for 7 minutes to obtain a green blank;
[0070] Step 3: Processing: cutting the green body to obtain a zirconia ceramic body;
[0071] Step 4: Sintering: Sinter the zirconia ceramic body at 1800° C. for 6 hours in a vacuum environment, cool naturally to room temperature, grind and polish to obtain a zirconia ceramic material.
[0072] The dispersant is composed of hydroxypropyl methylcellulose and polyvinyl alcohol in a mass ratio of 1:2.5.
[0073] The preparation method of the modified boron-doped molybdenum carbide comprises the following steps:
[0074] S1: molybdenum powder and carbon powder are uniformly mixed in a mass ratio of 2.5:1, anhydrous ethanol with a mass percentage of 16wt% of the molybdenum powder is added, and after grinding for 2h, the tablets are pressed at 180MPa for 6min, and then placed in an arc melting furnace for melting, the current is 800A, and the melting time is 5min, to obtain a Mo2C matrix;
[0075] S2 At room temperature, 14 parts by weight of the Mo2C matrix and 5 parts by weight of boric acid were ground together for 60 minutes, and then placed in a nitrogen atmosphere tube furnace at 900°C for calcination for 5 hours, cooled to room temperature, washed with a 5 mol / L NaOH aqueous solution, filtered and dried to obtain boron-doped molybdenum carbide;
[0076] S3: Disperse 10 parts by weight of the above-mentioned boron-doped molybdenum carbide in 160 parts by weight of a 65wt% ethanol aqueous solution, stir evenly, add 3 parts by weight of ammonia water and 2 parts by weight of tetraethyl orthosilicate, stir and react at 60°C and 700rpm for 8h, filter, wash and dry to obtain silica-coated boron-doped molybdenum carbide; add 2 parts by weight of N-(6-aminohexyl)aminomethyltriethoxysilane, stir at 55°C and 700rpm for 3h, centrifuge, wash and dry to obtain modified boron-doped molybdenum carbide.
[0077] Comparative Example 1
[0078] A method for preparing a zirconium oxide ceramic material comprises the following steps:
[0079] Step 1, mixing: 80 parts by weight of zirconium oxide, 8 parts by weight of molybdenum carbide, 2 parts by weight of carbon nanotubes, 3 parts by weight of cerium oxide, 7 parts by weight of dispersant, and 100 parts by weight of 50wt% ethanol aqueous solution are mixed and stirred to obtain a mixed solution; the mixed solution is placed in a ball mill for ball milling at a ball milling rate of 200r / min and a ball milling time of 3h to obtain a ball milled mixed solution;
[0080] Step 2, molding: the ball milled mixture is subjected to slip injection molding to obtain a wet blank, and then the wet blank is pressed by a hydraulic press at a pressure of 220PMa for 5 minutes to obtain a green blank;
[0081] Step 3: Processing: cutting the green body to obtain a zirconia ceramic body;
[0082] Step 4: Sintering: Sinter the zirconia ceramic body at 1650° C. for 5 h in a vacuum environment, cool naturally to room temperature, grind and polish to obtain a zirconia ceramic material.
[0083] The dispersant is composed of hydroxypropyl methylcellulose and polyvinyl alcohol in a mass ratio of 1:1.8.
[0084] The molybdenum carbide adopts commercially available molybdenum carbide.
[0085] Comparative Example 2
[0086] A method for preparing a zirconium oxide ceramic material comprises the following steps:
[0087] Step 1, mixing: 80 parts by weight of zirconium oxide, 8 parts by weight of boron-doped molybdenum carbide, 2 parts by weight of carbon nanotubes, 3 parts by weight of cerium oxide, 7 parts by weight of dispersant, and 100 parts by weight of 50wt% ethanol aqueous solution are mixed and stirred to obtain a mixed solution; the mixed solution is placed in a ball mill for ball milling at a ball milling rate of 200r / min and a ball milling time of 3h to obtain a ball milled mixed solution;
[0088] Step 2, molding: the ball milled mixture is subjected to slip injection molding to obtain a wet blank, and then the wet blank is pressed by a hydraulic press at a pressure of 220PMa for 5 minutes to obtain a green blank;
[0089] Step 3: Processing: cutting the green body to obtain a zirconia ceramic body;
[0090] Step 4: Sintering: Sinter the zirconia ceramic body at 1650° C. for 5 h in a vacuum environment, cool naturally to room temperature, grind and polish to obtain a zirconia ceramic material.
[0091] The dispersant is composed of hydroxypropyl methylcellulose and polyvinyl alcohol in a mass ratio of 1:1.8.
[0092] The method for preparing boron-doped molybdenum carbide comprises the following steps:
[0093] S1: molybdenum powder and carbon powder are uniformly mixed in a mass ratio of 2:1, anhydrous ethanol with a mass percentage of 10wt% of the molybdenum powder is added, and after grinding for 1 hour, the tablets are pressed at 150MPa for 4 minutes, and then placed in an arc melting furnace for melting, the current is 500A, and the melting time is 3 minutes to obtain a Mo2C matrix;
[0094] S2 At room temperature, 10 parts by weight of the above Mo2C matrix were ground together with 3 parts by weight of boric acid for 30 minutes, and then placed in a nitrogen atmosphere tubular furnace at 850°C for calcination for 3 hours, cooled to room temperature, washed with 4 mol / L NaOH aqueous solution, filtered and dried to obtain boron-doped molybdenum carbide.
[0095] Comparative Example 3
[0096] A method for preparing a zirconium oxide ceramic material comprises the following steps:
[0097] Step 1, mixing: 80 parts by weight of zirconium oxide, 8 parts by weight of modified boron-doped molybdenum carbide, 2 parts by weight of carbon nanotubes, 3 parts by weight of cerium oxide, 7 parts by weight of dispersant, and 100 parts by weight of 50wt% ethanol aqueous solution are mixed and stirred to obtain a mixed solution; the mixed solution is placed in a ball mill for ball milling at a ball milling rate of 200r / min and a ball milling time of 3h to obtain a ball milled mixed solution;
[0098] Step 2, molding: the ball milled mixture is subjected to slip injection molding to obtain a wet blank, and then the wet blank is pressed by a hydraulic press at a pressure of 220PMa for 5 minutes to obtain a green blank;
[0099] Step 3: Processing: cutting the green body to obtain a zirconia ceramic body;
[0100] Step 4: Sintering: Sinter the zirconia ceramic body at 1650° C. for 5 h in a vacuum environment, cool naturally to room temperature, grind and polish to obtain a zirconia ceramic material.
[0101] The dispersant is hypromellose.
[0102] The preparation method of the modified boron-doped molybdenum carbide comprises the following steps:
[0103] S1: molybdenum powder and carbon powder are uniformly mixed in a mass ratio of 2:1, anhydrous ethanol with a mass percentage of 10wt% of the molybdenum powder is added, and after grinding for 1 hour, the tablets are pressed at 150MPa for 4 minutes, and then placed in an arc melting furnace for melting, the current is 500A, and the melting time is 3 minutes to obtain a Mo2C matrix;
[0104] S2 At room temperature, 10 parts by weight of the above Mo2C matrix and 3 parts by weight of boric acid were ground together for 30 minutes, and then placed in a nitrogen atmosphere tube furnace at 850°C for calcination for 3 hours, cooled to room temperature, washed with 4 mol / L NaOH aqueous solution, filtered and dried to obtain boron-doped molybdenum carbide;
[0105] S3: Disperse 8 parts by weight of the above-mentioned boron-doped molybdenum carbide in 100 parts by weight of 60wt% ethanol aqueous solution, stir evenly, add 2 parts by weight of ammonia water and 1 part by weight of tetraethyl orthosilicate, stir and react at 50°C and 600rpm for 6h, filter, wash and dry to obtain silica-coated boron-doped molybdenum carbide; add 1 part by weight of N-(6-aminohexyl)aminomethyltriethoxysilane, stir at 50°C and 600rpm for 2h, centrifuge, wash and dry to obtain modified boron-doped molybdenum carbide.
[0106] Comparative Example 4
[0107] A method for preparing a zirconium oxide ceramic material comprises the following steps:
[0108] Step 1, mixing: 80 parts by weight of zirconium oxide, 8 parts by weight of modified boron-doped molybdenum carbide, 2 parts by weight of carbon nanotubes, 3 parts by weight of cerium oxide, 7 parts by weight of dispersant, and 100 parts by weight of 50wt% ethanol aqueous solution are mixed and stirred to obtain a mixed solution; the mixed solution is placed in a ball mill for ball milling at a ball milling rate of 200r / min and a ball milling time of 3h to obtain a ball milled mixed solution;
[0109] Step 2, molding: the ball milled mixture is subjected to slip injection molding to obtain a wet blank, and then the wet blank is pressed by a hydraulic press at a pressure of 220PMa for 5 minutes to obtain a green blank;
[0110] Step 3: Processing: cutting the green body to obtain a zirconia ceramic body;
[0111] Step 4: Sintering: Sinter the zirconia ceramic body at 1650° C. for 5 h in a vacuum environment, cool naturally to room temperature, grind and polish to obtain a zirconia ceramic material.
[0112] The dispersant is polyvinyl alcohol.
[0113] The preparation method of the modified boron-doped molybdenum carbide comprises the following steps:
[0114] S1: molybdenum powder and carbon powder are uniformly mixed in a mass ratio of 2:1, anhydrous ethanol with a mass percentage of 10wt% of the molybdenum powder is added, and after grinding for 1 hour, the tablets are pressed at 150MPa for 4 minutes, and then placed in an arc melting furnace for melting, the current is 500A, and the melting time is 3 minutes to obtain a Mo2C matrix;
[0115] S2 At room temperature, 10 parts by weight of the above Mo2C matrix and 3 parts by weight of boric acid were ground together for 30 minutes, and then placed in a nitrogen atmosphere tube furnace at 850°C for calcination for 3 hours, cooled to room temperature, washed with 4 mol / L NaOH aqueous solution, filtered and dried to obtain boron-doped molybdenum carbide;
[0116] S3: Disperse 8 parts by weight of the above-mentioned boron-doped molybdenum carbide in 100 parts by weight of 60wt% ethanol aqueous solution, stir evenly, add 2 parts by weight of ammonia water and 1 part by weight of tetraethyl orthosilicate, stir and react at 50°C and 600rpm for 6h, filter, wash and dry to obtain silica-coated boron-doped molybdenum carbide; add 1 part by weight of N-(6-aminohexyl)aminomethyltriethoxysilane, stir at 50°C and 600rpm for 2h, centrifuge, wash and dry to obtain modified boron-doped molybdenum carbide.
[0117] Test Example 1
[0118] 1. Bending strength test: The national standard GB / T6569-2006 "Test method for bending strength of fine ceramics" was used to measure the three-point bending strength of the zirconia ceramic material prepared by the present invention. The size of the sample was 40×3×4 mm, the span was 30 mm, the loading speed was 0.5 mm / min, the upper and lower rollers were kept clean, and there were no serious scratches on the surface. The lower roller needed to be contoured according to the contour of the finished product. Each group of samples was repeated 5 times and the average value was taken. The results are shown in Table 1.
[0119] 2. Vickers hardness: The Vickers hardness of the zirconia ceramic material prepared by the present invention was measured by the test method in the national standard QB / T4780-2015 "Method for Determining Vickers Hardness of Glaze Surface of Daily-use Ceramics", with 5 replicates for each group of samples and the average value was taken. The results are shown in Table 1.
[0120] Table 1 Mechanical properties test results of zirconia ceramic materials
[0121]
[0122] Test Example 2
[0123] Wear resistance test: Referring to the national standard "GT / T3810.7-2016 Ceramic Tile Test Method Part 7: Determination of Surface Wear Resistance of Glazed Tile", the wear resistance test of the zirconia ceramic material prepared above was carried out. The method was ground at 12,000 revolutions. The mass loss of the zirconia ceramic material prepared after firing under the same firing conditions is shown in Table 2 below.
[0124] Table 2 Wear resistance test results of zirconia ceramic materials
[0125]
[0126]
[0127] From the above results, it can be seen that the zirconia ceramic material prepared by the present invention has good mechanical properties. It can be seen from Example 1 and Comparative Examples 3-4 that when hydroxypropyl methylcellulose and polyvinyl alcohol are mixed, they can work together using their own different dispersion mechanisms to more effectively prevent the aggregation and sedimentation of zirconia and other solid particles, thereby improving the dispersion stability of the entire system, achieving uniform physical and chemical changes in the subsequent calcination process, thereby obtaining a uniform microstructure and better material properties, reducing the risk of pores and crack defects formed due to particle aggregation during the calcination process, and then improving the tighter stacking of ceramic materials, which helps to optimize the growth of grains, thereby obtaining a finer and uniform grain structure, and improving the strength, toughness and compactness of ceramic materials.
[0128] It can be seen from Example 1 and Comparative Examples 1-2 that boron doping can change the microstructure of molybdenum carbide and increase its toughness. Modified boron-doped molybdenum carbide is a hard material, and its addition can improve the hardness and wear resistance of zirconia ceramics, promote grain refinement in zirconia ceramics and enhance the interface bonding between different phases, thereby improving the uniformity and mechanical properties of the material, and also helping to improve the wear resistance and structural stability of the material. In addition, the addition of modified boron-doped molybdenum carbide helps to optimize the sintering process, may reduce the sintering temperature and increase the sintering rate, thereby saving energy and reducing production costs.
[0129] The introduction of silane coupling agent improves the dispersion of boron-doped molybdenum carbide in the zirconia ceramic matrix, reduces particle aggregation, makes the ceramic material more uniform in microstructure, and helps to improve the density and strength of the material; the modified boron-doped molybdenum carbide can serve as the core of grain boundary formation during calcination, promotes grain growth and grain boundary formation, and the increase in the number of grain boundaries can improve the strength and toughness of the material; the boron-doped molybdenum carbide modified by silane coupling agent can react chemically with the surface of zirconia particles in zirconia ceramics during calcination to form a strong chemical bond, which enhances the bonding force between particles and helps to improve the overall tightness of the ceramic material. In addition, during the calcination process, the silane coupling agent can reduce the pores and defects in the ceramic material. Since the silane coupling agent improves the bonding force between particles, it helps to discharge gas and close tiny pores during the sintering process, thereby reducing the porosity in the material, improving the density of the material, and improving the wear resistance.
Claims
1. A method for preparing a zirconium oxide ceramic material, characterized in that: The steps include: Step 1, mixing: mixing zirconium oxide, modified boron-doped molybdenum carbide, carbon nanotubes, cerium oxide, a dispersant, and an ethanol aqueous solution to obtain a mixed solution; ball-milling the mixed solution to obtain a ball-milled mixed solution; Step 2: Forming: The ball milled mixture is subjected to slip injection molding to obtain a wet blank, and then the wet blank is pressed by a hydraulic press to obtain a green blank; Step 3: Processing: cutting the green body to obtain a zirconia ceramic body; Step 4: Sintering: Sintering the zirconia ceramic body to obtain a zirconia ceramic material.
2. The method for preparing the zirconium oxide ceramic material according to claim 1, characterized in that: The ball milling rate in the step 1 is 160-240 r / min, and the ball milling time is 2-5 h.
3. The method for preparing the zirconium oxide ceramic material according to claim 1, characterized in that: The pressing pressure in the step 2 is 180-260PMa, and the pressing time is 3-7min.
4. The method for preparing the zirconium oxide ceramic material according to claim 1, characterized in that: The sintering temperature of step 4 is 1500-1800°C, and the sintering time is 3-6h.
5. The method for preparing the zirconium oxide ceramic material according to claim 1, characterized in that: The dispersant includes at least one of hydroxypropyl methylcellulose, polyacrylic acid, polyvinyl alcohol, polyethylene glycol, and ammonium polyacrylate.
6. The method for preparing the zirconia ceramic material according to claim 1, characterized in that: The preparation method of the modified boron-doped molybdenum carbide comprises the following steps: S1: uniformly mix molybdenum powder and carbon powder, add anhydrous ethanol to grind, press into tablets, and melt to obtain Mo2C matrix; S2. Grinding the above Mo2C matrix with boric acid, calcining in a tube furnace, cooling to room temperature, washing, filtering and drying to obtain boron-doped molybdenum carbide; S3: Disperse the above-mentioned boron-doped molybdenum carbide in an ethanol aqueous solution, stir evenly, add ammonia water and tetraethyl orthosilicate to stir and react, filter, wash, and dry to obtain silica-coated boron-doped molybdenum carbide; add N-(6-aminohexyl)aminomethyltriethoxysilane and stir to obtain modified boron-doped molybdenum carbide.
7. The method for preparing the zirconia ceramic material according to claim 6, characterized in that: In the S1, the tableting pressure is 120-180 MPa, and the tableting time is 2-6 min; the smelting current is 400-800 A, and the smelting time is 1-5 min.
8. The method for preparing the zirconia ceramic material according to claim 6, characterized in that: The calcination temperature in S2 is 800-900° C., and the calcination time is 2-5 hours.
9. The method for preparing the zirconium oxide ceramic material according to claim 6, characterized in that: The heating and stirring temperature in S3 is 45-60° C., the stirring speed is 400-700 rpm, and the stirring time is 4-8 h.
10. A zirconia ceramic material, characterized in that: The method is obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Zirconia ceramic for oil / gas well and preparation method of zirconia ceramic
CN106830930A
High-strength easily-colored novel ceramic
CN108727052A
Preparation method of nickel-doped molybdenum carbide nano-sheets
CN109759103A
Ultrahigh-strength, high-toughness and low-density zirconia ceramic as well as preparation method and application thereof
CN114516754A
Preparation method and application of boron and nitrogen co-doped molybdenum carbide
CN116654937A
Cited By
Nano ceramic grinding material and preparation method thereof
CN121063952A
